Combined creep and hydrogen attack of petro refinery steel - ANDREW BAKER (2021)
The thesis is based on the study of the interaction between creep and hydrogen attack, with particular emphasis on the commonly used 2.25Cr-lMo steel. The driving force for the work is the petrochemical industry, where large steel reactor vessels used for hydro-cracking and other processes, are known to suffer damage by hydrogen attack. Currently, no reliable method exists for determining the lifetime of these vessels, due partially to the difficulty of obtaining experimental data under the necessary' high hydrogen pressures and temperatures.A large part of the thesis involved the design and building of unique, high-tech testing facilities which could operate safely and accurately under the severe conditions required for such a study. The test rigs were then used to perform both simple uniaxial creep and internally pressurised tube tests in hydrogen environments. Pressurised tubes were used to provide a stress-state more closely related to that found in industrial components. Such experiments allow more accurate extrapolation to industrial pressure vessel behaviour than would be possible with uniaxial data alone.The creep results, together with careful metallography, showed the damaging effect of hydrogen attack on creep life and ductility, or conversely, the accelerating effect of applied stress on hydrogen attack. Tube testing revealed an effect of the multiaxial stress and demonstrated the importance of the hydrogen concentration in the steel.The above results were used to develop a Continuum Damage Mechanics (CDM) model for the prediction of tubular behaviour when pressurised with hydrogen. Within the range of conditions studied, the model was successful and further creep testing work is suggested to verify and develop the model further, as well as to study in greater detail the hydrogen attack mechanisms.